"You can't chain a dog to a porch": a multisite qualitative analysis of youth narratives of parental approaches to substance use - Allie Slemon; Emily K. Jenkins; Rebecca J. Haines-Saah; Zachary Daly; Sunny Jiao (BMC, 2019)
Abstract Background Reducing harms of youth substance use is a global priority, with parents identified as a key target for efforts to mitigate these harms. Much of the research informing parental responses to youth substance use are grounded in abstinence and critiqued as ineffective and unresponsive to youth contexts. Parental provision of substances, particularly alcohol, is a widely used approach, which some parents adopt in an attempt to minimize substance use harms; however, research indicates that this practice may actually increase harms. There is an absence of research exploring youth perspectives on parental approaches to substance use or the approaches youth find helpful in minimizing substance use-related harms. Methods This paper draws on interviews with youth aged 13-18 (N = 89) conducted within the Researching Adolescent Distress and Resilience (RADAR) study in three communities in British Columbia, Canada. An ethnographic approach was used to explore youth perspectives on mental health and substance use within intersecting family, social, and community contexts. This analysis drew on interview data relating to youth perspectives on parental approaches to substance use. A multisite qualitative analysis (MSQA) was conducted to examine themes within each research site and between all three sites to understand how youth perceive and respond to parental approaches to substance use in different risk environment contexts. Results Within each site, youths' experiences of and perspectives on substance use were shaped by their parents' approaches, which were in turn situated within local social, geographic, and economic community contexts. Youth descriptions of parental approaches varied by site, though across all sites, youth articulated that the most effective approaches were those that resonated with the realities of their lives. Zero-tolerance approaches were identified as unhelpful and unresponsive, while approaches that were aligned with harm reduction principles were viewed as relevant and supportive. Conclusions Youth perspectives illustrate that parental approaches to substance use that are grounded in harm reduction principles resonate with young people's actual experiences and can support the minimization of harms associated with substance use. Evidence-based guidance is needed that supports parents and young people in adopting more contextually responsive harm reduction approaches to youth substance use.